2015
DOI: 10.1097/wno.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Optic Perineuritis in Behçet Disease

Abstract: OPN may occur as a manifestation of BD and, in non-Western countries, this may be more common than the idiopathic variety. In contrast to idiopathic cases, OPN in BD is more likely to demonstrate initial rapid progression of visual loss and more severe loss at presentation. Patients show less recovery of vision in response to corticosteroids but carry a lower rate of subsequent relapse. Patients with OPN should be specifically questioned regarding symptoms of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…It is a great mimicker of typical ON. OPN has been reported mostly as idiopathic and isolated cases [1] although associations with other diseases such as Wegener granulomatosis [2], giant cell arteritis [3], Crohn’s disease [4], Behcet disease [5], leukemia [6] and acute retinal necrosis [7] have been reported. To the best of our knowledge, there are limited reports of OPN in patients with NMO or NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…It is a great mimicker of typical ON. OPN has been reported mostly as idiopathic and isolated cases [1] although associations with other diseases such as Wegener granulomatosis [2], giant cell arteritis [3], Crohn’s disease [4], Behcet disease [5], leukemia [6] and acute retinal necrosis [7] have been reported. To the best of our knowledge, there are limited reports of OPN in patients with NMO or NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Medical history, physical examination, and laboratory tests 15 were used to exclude multiple sclerosis, neuromyelitis optica, sarcoidosis, and other vasculitis, as well as infectious diseases such as syphilis, tuberculosis, and herpes virus.…”
Section: Methodsmentioning
confidence: 99%
“…The International Criteria for Behçet’s Disease (ICBD) integrated neurological manifestations into a scoring system 14 and is helpful for early diagnosis of primary optic neuropathy in Behçet’s syndrome. Lai et al 15 reported 10 Chinese patients who met ICBD (see online supplementary Table 1) and demonstrated optic perineuritis on MRI imaging. The current study collected the data of patients with primary optic neuropathy in Behçet’s syndrome meeting ICBD to report their clinical characteristics, MRI findings, and short-term visual prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Optic perineuritis (OPN), a rare disease in clinic, is an in ammatory disorder characteristic of the optic nerve sheath enhancement, which was rstly reported by Purvin in 1883 1,2 . Most OPN were unilateral idiopathic, and some patients were associated with infection and autoimmune diseases [3][4][5][6][7][8][9][10][11][12][13][14] , speci cally including Behçet syndrome 3,4 , syphilis 5 , herpes zoster 6 , tuberculosis 7 , sarcoidosis [8][9] , Wegener granulomatosis 10 , giant cell arteritis 11 and Crohn's disease 12 and so on 13,14 . And the hyaluronic acid injections can also cause OPN 15 .…”
Section: Introductionmentioning
confidence: 99%